2015
DOI: 10.1007/s40616-014-0023-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Modified Chaining Procedure with Textual Prompts to Establish Intraverbal Storytelling

Abstract: Echoic, tact, and textual transfer procedures have been proven successful in establishing simple intraverbals (Braam and Poling Applied Research in Mental Retardation, 4, 279-302, 1983; Luciano Applied Research in Mental Retardation, 102, 346-357, 1986; Watkins et al. The Analysis of Verbal Behavior, 7, 69-81, 1989). However, these strategies may be ineffective for some children due to the complexity of the targeted intraverbals. The current study investigated the use of a novel procedure which included a modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 14 publications
2
18
0
8
Order By: Relevance
“…In nine studies, statements were reported as the vocal S D . Three of the studies included both questions and statements as the S D (Emmick, Cihon, & Eshleman, 2010;Feng et al, 2015;Valentino, Conine, Delfs, & Furlow, 2015) and one study involved a single word as the S D (Allan, Vladescu, Kisamore, Reeve, & Sidener, 2015). One to seventy-eight different questions or statements as S D s were included in the sampled studies.…”
Section: Types Of Discriminative Stimulimentioning
confidence: 99%
“…In nine studies, statements were reported as the vocal S D . Three of the studies included both questions and statements as the S D (Emmick, Cihon, & Eshleman, 2010;Feng et al, 2015;Valentino, Conine, Delfs, & Furlow, 2015) and one study involved a single word as the S D (Allan, Vladescu, Kisamore, Reeve, & Sidener, 2015). One to seventy-eight different questions or statements as S D s were included in the sampled studies.…”
Section: Types Of Discriminative Stimulimentioning
confidence: 99%
“…(Finkel & Williams, 2001;Ingvarsson & Hollobaugh, 2011;Kodak & Paden, 2015;Matos, Cordeiro, et al, 2020;Matos, Cruz, et al, 2020;Sundberg & Sundberg, 1990); (2) relatar nomes de itens pertencentes a diferentes categorias como, por exemplo, dizer "águia" diante de "diga-me o nome de um animal voador" (Cordeiro, 2021;Grannan & Rehfeldt, 2012;Matos, Aragão & Matos, 2019;Matos, Araújo & Silva, 2018;Matos & Lima, 2018;Miguel, Petursdottir, & Carr, 2005;Partington & Bailey, 1993;Petursdottir, Carr, Lechago, & Almason, 2008); (3) intraverbais com elementos nas funções reversas de estímulo-resposta como, por exemplo, dizer "cheio" diante da instrução "diga-me o oposto de vazio" (Pérez-González, García-Asenjo, Williams, & Carnerero, 2007; Pérez-González, Salameh, & García-Asenjo, 2018); (4) intraverbais representando equivalência entre palavras em língua nativa e estrangeira como, por exemplo, dizer "naranja" diante de "como se diz laranja em espanhol?" (Cortez, dos Santos, Quintal, Silveira, & de Rose, 2020;Petursdottir, Ólafsdottir, & Aradóttir, 2008;Petursdottir & Haflidadóttir, 2009); 5) intraverbais com três elementos verbais relacionados uns aos outros como, por exemplo, dizer "Argentina" diante de "diga-me o nome do país onde fica o parque El Botánico", após aprender a dizer "Buenos Aires" diante de "diga-me o nome de uma cidade da Argentina" e dizer "El Botánico" diante de "diga-me o nome de um parque em Buenos Aires" (Belloso-Díaz & Pérez-González, 2015); (6) recontar histórias com encadeamento lógico entre suas partes (e.g., diante de "conte-me a história do menino João", uma criança diz "ele acordou cedo, tomou banho, vestiu-se, tomou café e foi para a escola") (Matos, Araújo & Costa, 2019;Matos, Guimarães, Sousa & Matos, 2019;Matos, Matos & Figueiredo, 2017;Valentino, Conine, Delfs & Furlow, 2015).…”
Section: Introductionunclassified
“…Portanto, aspectos metodológicos e resultados de pesquisas mencionadas a esse respeito são discutidos, a seguir, sendo que todas compreenderam estratégias de promoção de mudança de controle de estímulos para aquisição de intraverbais. Valentino et al (2015) avaliaram os efeitos de um procedimento de ensino de repertórios de recontar histórias em três crianças com TEA, e com idades variando entre 4 e 8 anos. As histórias foram construídas por meio de imagens retratando cenas/ações (e.g., imagem de uma criança tomando seu café da manhã).…”
Section: Introductionunclassified
“…"; Finkel & Williams, 2001), provide multiple answers for categories (e.g., "What are some animals? "; Carroll & Kodak, 2015), respond to yes-no questions (e.g., Shillingsburg, Kelley, Roane, Kisamore, & Brown, 2009), and tell stories (Valentino et al, 2015). These studies provide a small demonstration of the variety of topographies and levels of complexity of intraverbal response.…”
Section: Intraverbalsmentioning
confidence: 87%
“…Five studies focused on response variability (Carroll & Kodak, 2015;Contreras & Betz, 2016) and the training of advanced intraverbal repertoires (e.g., storytelling; Valentino, Conine, Delfs, & Furlow, 2015). For example, Kisamore, Karsten, and Mann (2016) compared the effects of trial-and-error training, differential observing response (DOR), and DOR plus trial-blocking procedures to teach intraverbal responses under multiple control to five children between the ages of 4 and 12 who had been diagnosed with ASD.…”
Section: Intraverbalsmentioning
confidence: 99%